Fast and low power integrated circuit for impulsive sound localisation using Kalman filter approach - Chacón Rodríguez, A. (2010)
A fast low power time delay estimator for the localisation of impulsive sounds is shown. The system is based on a simplified Kalman filter structure and is implemented on a 0.5 m standard CMOS architecture. Tests show that the circuit is faster than equivalent systems, and that its energy requirements are lower than the best results reported so far.